Linear Relative n-Widths for Linear Operators Preserving an Intersection of Cones - S. P. Sidorov (International Journal of Mathematics and Mathematical Sciences)
We introduce the definition of linear relative n-width and find estimates of linear relative n-widths for linear operators preserving the intersection of cones of p-monotonicity functions.